Implementation of Anesthesia Ethics to Improve Medical Professionalism - Aulia Wiratama Putra (Indonesian Health Journal, 2023)
This research aims to increase the professionalism of medical personnel in the field of medicine, especially poly surgery. Research methodology with descriptive qualitative literature review design. Data collection techniques by collecting information from electronic reading sources. This type of research is an analysis of medical journals with primary subjects from several hospitals in Indonesia for analysis based on inclusion criteria such as patients experiencing postoperative anxiety and insecurity, this results in weak physical health due to psychological influences. Data analysis using source triangulation. The research results describe that the medical and health sciences field has ethics and a professional attitude that needs to be realized to increase a sense of comfort and trust in the medical world. From the results of several findings, it was stated that the action decisions taken by medical science were still in agreement or had yet to be mutually agreed upon. They emphasise the element of compulsion because of the conditions requiring it. Patients do not have a voluntary attitude in agreeing to medical action. Such influence becomes a consideration that rules and agreements, the volunteers of doctors and patients must be realized with awareness and voluntarism. If two things are realized, it can increase the value of medical professionalism, especially in anaesthesia.